Learner engagement in the flipped foreign language classroom: Definitions, debates, and directions of future research - Li, Zhiyong; Li, Jiaying (Frontiers in Psychology, 2022)
Flipped classrooms have attracted widespread attention and interest from EFL practitioners and researchers and are regarded as a promising pedagogical approach to increase learning outcomes and facilitate learner engagement. This article takes stock of the publications on learner engagement in the flipped English for foreign language (EFL) classrooms. In so doing, we aim to clarify the engagement construct specific to the EFL classroom setting, summarise the impact that flipped classrooms have on EFL learners’ engagement and identify factors affecting learner engagement. We find that there has been a range of debates and tensions regarding flipped classrooms and learner engagement in the EFL setting, and more theory-grounded empirical study is needed to delineate learner engagement and flipped classrooms as situated in the specific learning and teaching context. We would argue that in future research, multiple variables, including learner dynamics and social-psychological factors, should be considered while flipping the EFL course so that practitioners can provide tailor-made support to improve learners’ engagement.